Kedudukan Anak Perempuan Dalam Pembagian Harta Warisan Menurut Hukum Adat Timor Dalam Prespektif Gender Di Desa Baumata Kecamatan Taebenu, Kabupaten Kupang - Aprilia Yosinta Trinata Tabelak; Sukardan Aloysius; Yossie M.Jacob (Hakim, 2023)
Gender's existence today is strongly influenced in every aspect of human life. One of them is the application of gender in customary inheritance law in Baumata Village, Taebenu District, Kupang Regency. This type of research is empirical research conducted in Baumata Village, Taebenu District, Kupang Regency and the data source used is primary data. Primary data is data obtained directly from the research location through direct interviews with respondents. Based on the results of this study is that the Baumata village community still maintains the position of inheritance rights, namely boys are still more dominant in getting inheritance rights but not to get the inheritance rights. The timor community in baumata village still maintains the inheritance rights distribution system because it still adheres to patrilineal culture.